Debating Stephen Hawkingâ€™s Thought on Creation of Universe: A Qurâ€™anic Scientific Interpretation Perspective - Adi, Deki Ridho; Asnawi, Aqdi Rofiq; Hidayaturrohmah, Nur (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Stephen Hawkingâ€™s theory â€œMâ€ posits that the universe was formed without the assistance of God. This paper elaborates the qurâ€™anic position on Hawkingâ€™s idea by analyzing the qurâ€™anic scientific interpretation of universe creation. Therefore, the literature review was utilized to collect as much data as feasible, which was then evaluated using the descriptive-analytical method. The findings of this study indicate that Stephen Hawkingâ€™s â€œMâ€ hypothesis has three faults, which constitute a scientific critique of the interpretation of Qurâ€™anic texts relating to the earth and sky. The three faults are: 1) Earth and sky were not created without Godâ€™s intervention, as Hawking claimed, but by the will and strength of Allah. This finding is stated in the interpretation of Surah Al-Anbiyaâ€™ verse 30, Al-Fushshilat verse 10, and Al-Aâ€™raf verse 54. 2) Hawkingâ€™s concept of creation is inappropriate since it is based on the rationalism of liberal thought. The natural creation process described in the Qurâ€™an, scientifically proved by science, differs from Hawkingâ€™s claim. 3) Hawkingâ€™s idea of a mechanism for creating the heavens and the earth is not suitable with the scientific facts regarding them stated in the Qurâ€™anâ€™s scientific interpretation